ANALISIS PENGARUH SIZE, CAPITAL ADEQUACY RATIO (CAR), RETURN ON ASSETS (ROA), NON PERFORMING LOAN (NPL), DAN INFLASI TERHADAP LOAN TO DEPOSIT RATIO (LDR) - Ramadhani, Aulia Nazala; Indriani, Astiwi (Faculty of Economics and Business Diponegoro University, 2016)
This research was conducted to examine the influence of the size, Capital Adequacy Ratio (CAR), Return On Assets (ROA), Non Performing Loan (NPL), and inflation toward Loan to Deposit Ratio (ROA).The population of this research is the conventional commercial bank listed on the Indonesia Stock Exchange period 2010 through 2014. Purposive sampling method were used as samples determining method and 21 banks selected as the sample of this research. Analysis Method with multilinier regression of ordinary least square and hypotheses test used t-statistic and F-statistic at level significance 5%, a classic assumption examination which consist of normality test, multicolinearity test, heteroscedasticity test and autocorrelation test is also being done to test the hypothese.The results of the research simultantly using F test, showed that size, Capital Adequacy Ratio (CAR), Return On Assets (ROA), Non Performing Loan (NPL), and inflation variables influence significantly toward Loan to Deposit Ratio (LDR). Partially varibles using t test, showed size is not significant negative influence on the LDR with a significance level of 0,705 > 0,050, CAR is not significant positive influence on the LDR with a significance level of 0,801 > 0,050, ROA is not significant positive influence on the LDR with a significance level of 0,973 > 0,050, NPL is significance negative influence on the LDR with a significance level of 0,017 < 0,050, and inflation is significant positive influence on the LDR with a significance level of 0,009 < 0,050. The coefficient determinant (r square) is 0,238 which means 23,8% LDR variation explained by size, CAR, ROA, NPL, and inflation, whereas 76,2% explained by another variables which was not to be entered in the research model.